2015
DOI: 10.1007/s00384-015-2333-4
|View full text |Cite
|
Sign up to set email alerts
|

Type D personality is associated with delaying patients to medical assessment and poor quality of life among rectal cancer survivors

Abstract: Type D personality was associated with poor QoL and mental health status among survivors of rectal cancer, even after adjustment for confounding background variables. Type D personality might be a general vulnerability factor to screen for subgroups at risk for longer symptom duration and emergency admissions in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The prevalence of type‐D personality among patients with primary brain tumours was 34.1% in this study. This is higher than the prevalence identified in patients with gastric cancer (23%; Zhang et al, 2016) and colorectal cancer (21.0%; Husson et al, 2017), or in survivors of various types of cancer including endometrial cancer, colorectal cancer, lymphoma and multiple myeloma (19%; Mols et al, 2012). Compared to other patients with chronic disease in the Korean population, the prevalence of type‐D personality in patients with brain tumours was lower than in patients with recurrent coronary artery disease (46.7%; Jo et al, 2019) and patients receiving chemotherapy for ovarian cancer (56.0%; Kim et al, 2018), but higher than in patients with Parkinson's disease (19.9%; Kim et al, 2017a) and end‐stage renal disease (26.0%; Son et al, 2012).…”
Section: Discussionmentioning
confidence: 70%
“…The prevalence of type‐D personality among patients with primary brain tumours was 34.1% in this study. This is higher than the prevalence identified in patients with gastric cancer (23%; Zhang et al, 2016) and colorectal cancer (21.0%; Husson et al, 2017), or in survivors of various types of cancer including endometrial cancer, colorectal cancer, lymphoma and multiple myeloma (19%; Mols et al, 2012). Compared to other patients with chronic disease in the Korean population, the prevalence of type‐D personality in patients with brain tumours was lower than in patients with recurrent coronary artery disease (46.7%; Jo et al, 2019) and patients receiving chemotherapy for ovarian cancer (56.0%; Kim et al, 2018), but higher than in patients with Parkinson's disease (19.9%; Kim et al, 2017a) and end‐stage renal disease (26.0%; Son et al, 2012).…”
Section: Discussionmentioning
confidence: 70%
“…For example, there is evidence of the role of personality characteristics [such as emotional lability, extraversion, openness to experience, agreeableness, conscientiousness (Paika et al, 2010 ), denial and sense of coherence (Hyphantis et al, 2011 ), repression and sense of coherence (Glavić et al, 2014 ) or neuroticism (Ristvedt and Trinkaus, 2005 )] in predicting Quality of Life (QoL) and illness perception (Mols et al, 2012a ; Schoormans et al, 2017 ) after cancer and related treatments. In other studies, Type D Personality and its components (negative affectivity and social inhibition) were associated with all-cause mortality (Shun et al, 2011 ), worse QoL in different domains (Shun et al, 2011 ; Mols et al, 2012b ; Husson et al, 2015 ; Zhang et al, 2016 ) and most disease-specific symptoms (Zhang et al, 2016 ) in CRC patients. Beside the importance of personality in coping with cancer after a diagnosis, this review wants to focus on personality as a contributing risk factor for the incidence of CRC.…”
Section: Introductionmentioning
confidence: 88%
“…Recent evidence has indicated that assessment of health-related quality of life (HR-QoL) may provide valuable information to improve risk assessment in CRC [4]. Evidence-based findings indicate that physical and psychosocial factors other than sociodemographic or clinical variables are associated with increased risk of impaired HR-QoL [5] and may predict CRC survival [68]. From a clinical perspective, HR-QoL as complementary data with clinical factors can help to screen for at risk sub-populations with physical or psychosocial issues that may benefit from enhanced monitoring or improved care management.…”
Section: Introductionmentioning
confidence: 99%